OEDOGONIALES FROM DHULE AND NANDURBAR DISTRICT, MAHARASHTRA (INDIA) - Dhale, Datta Asaram (Current Botany, 2017)
During the study of systematic account Oedogoniales of Sakri and Navapur taluka, district Dhule and Nandurbar respectively, Maharashtra the author collected twenty-three taxa belonging to three genera.Â Oedogonium Hirn. is a dominant genus followed by Bulbochaete Hirn. while Oedocladium Hirn. is a monotypic. Out of twenty-three taxa Oedogonium orientale Jao and Bulbochaete borealis Hirn., are first time recorded from India. Four taxa are new record for Maharashtra and twelve taxa were recorded second time from Maharashtra. The Oedogoniales of this region have not been studied earlier. This is the first ever attempt to explore, enumerate and taxonomically evaluate the algal components of the area. Distribution of the taxa in India has been discussed. The quantitative availability of species is also noted.Â